2021
DOI: 10.3390/polym13121941
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pollutant Gases on Surfactant Migration in Acrylic Emulsion Films: A Comparative Study and Preliminary Evaluation of Surface Cleaning

Abstract: From their first employment in the 1950s, acrylic emulsions have remained widely used as art material today. Although under certain deteriorating conditions they are very stable, if exposed to high humidity and atmospheric pollutant gases, their structural and chemical conformation is strongly affected. Dealing with the resulting surfactant migration, various cleaning treatments were considered over the years. However, their choice remains difficult as they easily alter the acrylic component, especially if in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…It was characterized as nBA/MMA as it shows C-H bond stretching vibrations (at 2956-2875 cm −1 ), C=O stretching (at 1726 cm −1 ), CH 2 -and -CH 3 bending vibrations (1452 and 1386 cm −1 , respectively), and the C-O-C and C-O stretching bands (at 1236, 1160, 1146 cm −1 ) in the fingerprint region [46,59,60]. Furthermore, the spectral signal of a surfactant, namely PEO (polyethylene oxide), was identified by the three characteristic absorbance bands at 2891, 1343, and 1112 cm −1 [61,62].…”
Section: Atr-ftir Results Of Acrylicsmentioning
confidence: 99%
“…It was characterized as nBA/MMA as it shows C-H bond stretching vibrations (at 2956-2875 cm −1 ), C=O stretching (at 1726 cm −1 ), CH 2 -and -CH 3 bending vibrations (1452 and 1386 cm −1 , respectively), and the C-O-C and C-O stretching bands (at 1236, 1160, 1146 cm −1 ) in the fingerprint region [46,59,60]. Furthermore, the spectral signal of a surfactant, namely PEO (polyethylene oxide), was identified by the three characteristic absorbance bands at 2891, 1343, and 1112 cm −1 [61,62].…”
Section: Atr-ftir Results Of Acrylicsmentioning
confidence: 99%
“…Furthermore, they can form micelles, resulting in a stabilising effect in paints. The two most studied and identified examples in modern paints are polyethylene glycol (PEG) and polyethylene oxide (PEO) [44,45]. (5) Surface modifying agents.…”
Section: Paint Formulations Used For Street Artmentioning
confidence: 99%
“…In addition, thermal stresses tend to expand and shrink paint layers, inducing the mechanical failure. In drastic outdoor conditions and sunlight exposure, additives (such as surfactants and plasticisers) can migrate towards the surface following the cracks network and then be removed by rain, leading to a more brittle and fragile paint film, devoid of the plasticisers [32,45,50]. Equally, studies described the migration to the surface of the paint layer of inorganic additives of the paint itself or from background layers (as preparatory layers or underlying paints) [52], in particular, it has been observed that thinner paint layers (as the one produced by spray paints) are more susceptible to this phenomenon [50].…”
Section: Effects Of Outdoor Exposure On Street Artworkmentioning
confidence: 99%